Calcium pyrophosphate crystal deposition disease: diagnosis and treatment - Rosales-Alexander JL (Dove Medical Press, 2014)
José Luis Rosales-Alexander,1 Jerónimo Balsalobre Aznar,1 César Magro-Checa2 1Rheumatology Department, Hospiten Ramblas, Santa Cruz de Tenerife, 2Rheumatology Department, San Cecilio University Hospital, Granada, Spain Abstract: Calcium pyrophosphate dihydrate crystal deposition disease (CPPD) is an inflammatory arthritis produced by the deposition of calcium pyrophosphate (CPP) crystals in the synovium and periarticular soft tissues. It is the third most common inflammatory arthritis. Diagnosis is suspected on the basis of the clinical picture and radiographic/laboratory findings. The reference standard for the diagnosis of CPPD is based on the identification of CPP crystals in synovial fluid by light microscopy, compensated polarized light microscopy, or phase contrast microscopy. Most treatment approaches for CPPD are based upon clinical experience and not upon controlled trials. They range – depending on the subtype and the characteristics of symptoms – from no treatment to interleukin-1 blockade antibodies or specific therapy for an underlying disease. This review summarizes all we know so far about the diagnosis and management of CPPD. Keywords: calcium pyrophosphate dihydrate deposition disease, CPPD, chondrocalcinosis, crystal-induced arthritides